Amputation of multiple limbs caused by use of inotropics: Case report, a report of 4 cases. Issue 5 (February 2018) - Jung, Ki Jin; Nho, Jae-Hwi; Cho, Hyeung-Kyu; Hong, Sijohn; Won, Sung Hun; Chun, Dong-Il; Kim, Byungsung
Abstract: Rationale: We present 4 cases of symmetrical peripheral gangrene (SPG) associated with use of inotropic agent to elevate blood pressure. SPG is a relatively rare phenomenon characterized by symmetrical distal ischemic damage that leads to gangrene of 2 or more sites in the absence of large blood vessel obstruction, where vasoconstriction rather than thrombosis is implicated as the underlying pathophysiology. We present 4 SPG cases of the multiple limbs amputation, associated with inevitable use of inotropic agents. Patient concerns: Inotropic agents including dopamine and norepinephrine are used frequently in the treatment of hypotension, and its effectiveness in treating shock is firmly established. However, it can be caused peripheral gangrene by prolonged administration of high dose inotropics, inducing the constant contraction of the peripheral blood vessels. Diagnosis: These 4 patients had different clinical histories and background factors, but each experienced sepsis. The level of amputation is determined by the line of demarcation in concert with considerations of the biomechanics of stump stability, weight bearing, and ambulation. Interventions: After recovering of general conditions and completion of demarcation, these 4 patients underwent the amputation of multiple limbs.(bilateral amputations of upper extremities or bilateral amputations of lower extremities). Outcomes: In each patient, there was no additional amputation caused by extension of SPG, and the rehabilitation with appropriate orthosis was performed. Treatment of underlying disease were continued too. Lessons: It is important to alert the possibility of amputations, according to the use of inevitable inotropics. We recommended the careful use of the inotropic agents to the physicians in treating septic shock.